2016
DOI: 10.1167/iovs.15-18291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dorzolamide on Retinal and Choroidal Blood Flow in the DBA/2J Mouse Model of Glaucoma

Abstract: PurposeTo test the hypothesis that acute topical dorzolamide (DZ) decreases intraocular pressure (IOP) and increases retinal and choroidal blood flow in the DBA/2J mouse model of glaucoma.MethodsRetinal and choroidal blood flow were measured in 4- and 9-month-old DBA/2J mice, and 4-month C57BL/6 (control) mice under isoflurane anesthesia using magnetic resonance imaging. Ocular blood flow was measured at baseline, and 1 and 2 hours after topical dorzolamide. Intraocular pressure was measured using a rebound to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
2
7
0
1
Order By: Relevance
“…For instance, melatonin or its analogue 5-MCA-NAT reduced IOP between 29 and 32% in the DBA/2J and, as happened in the present paper, the effect on the normotensive animal was not so marked [27]. Other authors who used classical compounds such as the carbonic anhydrase inhibitor dorzolamide have demonstrated a similar effect [28], reducing IOP. These authors observed reductions of approximately 60%, which are far from the ones here described.…”
Section: Discussionsupporting
confidence: 81%
“…For instance, melatonin or its analogue 5-MCA-NAT reduced IOP between 29 and 32% in the DBA/2J and, as happened in the present paper, the effect on the normotensive animal was not so marked [27]. Other authors who used classical compounds such as the carbonic anhydrase inhibitor dorzolamide have demonstrated a similar effect [28], reducing IOP. These authors observed reductions of approximately 60%, which are far from the ones here described.…”
Section: Discussionsupporting
confidence: 81%
“…Apart from lowering intraocular pressure, the drugs used in glaucoma therapy may additionally improve blood perfusion in the eye (87). Such an effect is caused by carbonic anhydrase inhibitors (88). An improvement in ocular circulation was also noted in the case of latanoprost (89,90).…”
Section: Neuroprotection To Counteract Vascular Deregulationmentioning
confidence: 86%
“…At the same time, the main focus of our current study was on the age- and IOP-related changes in the same animals, or animals from the same species. While both direct and indirect comparisons of D2 and B6 mice have been used in this and other MRI- and non-MRI based studies of visual pathway changes 17 , 24 , 30 , 70 78 , future studies should also consider comparing D2 mice with the age- and genetically-matched DBA/2J-Gpnmb+/SjJ mice, both male and female. On the other hand.…”
Section: Discussionmentioning
confidence: 99%